The Mental Structure of Assessment as a Linguistic and Synergetic Phenomenon - Prokhorova, Olga N.; Chekulai, Igor V.; Baghana, Jerôme; Kuprieva, Irina A.; Peresypkin, Andrey P. (Journal of History Culture and Art Research, 2017)
The article deals with the problems of the term mental structure of assessment seen as the main epistemic model in the consciousness of every representative of society on the one hand, and on the other – as a synergetic tool for linguistic analysis of lexical meaning and its connotation as the means of social attitude verbalization. The mental structure of assessment is a concept, which due to its positive features resembles the non-linear open synergetic system. Special attention in this article is paid to the transmission of sense in the discourse as the basic means of understanding connotations and change of lexical semantics.